Writing and Worship in Deng Zhimo’s Saints Trilogy - Ganany, Noga (Religions, 2022)
Around the turn of the seventeenth century, the prolific writer-editor Deng Zhimo produced three illustrated books narrating the lives of Lü Dongbin (The Flying Sword), Xu Xun (The Iron Tree), and Sa Shoujian (The Enchanted Date). This article focuses on the textual hybridity of Deng Zhimo’s hagiographic Saints Trilogy and argues that it offers encyclopedic, practical, and entertaining guidebooks for worshipping the three immortals and pursuing Daoist attainment. The cultic lore woven into the fabric of Deng’s Saints Trilogy reflects the important contribution of authors and publishers to popular reverence, highlighting the close interplay between "literature" and "religion" in late-imperial China.